The Control of Heat Radiation and Noise Performed by One of the Ship Production Companies in Indonesia - Tri Meidya Rahmawati; Nidia Nuraini (Universitas Airlangga, 2020)
Introduction: Noise is unwanted sound which comes from various working tools that can cause hearing loss on workers expressed in decibels (dB). The ambient noise value in the workplace is 85 dBA. Ambient temperature in the workplace that is too hot is dangerous for the health of individual workers because it can result in various mental and physical health disorders. Methods: This research was conducted at one of the Ship Production Companies in Indonesia in March to June 2018. This type of research was descriptive and the design of this study was cross-sectional. The variables of this research were technical control, administrative control, and PPE control. The purpose of this study was to describe the efforts of controlling one of the Ship Production Companies in Indonesia in controlling heat stress and noise. The data used were primary data and secondary data. Result: One of the Ship Production Companies in Indonesia still had high heat and noise pressure. Three control efforts have been made including administrative control, technical control, and the use of PPE. The results shown in terms of technical control still did not meet the requirements because not all technical efforts were made. Meanwhile, administrative control and PPE control have met the requirements. Conclusion: Among the three control efforts that have not met the requirements yet are technical licensing while those that have met the requirements are administrative control requirements and the use of PPE.Keywords: heat radiation, noise, ship production